(2x+6)+(5x-12)=99

Simple and best practice solution for (2x+6)+(5x-12)=99 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+6)+(5x-12)=99 equation:


(2x+6)+(5x-12)=99

We simplify the equation to the form, which is simple to understand
(2x+6)+(5x-12)=99

Remove unnecessary parentheses
2x+6+(5x-12)=99

Remove unnecessary parentheses
+2x+6+5x-12=+99

We move all terms containing x to the left and all other terms to the right.
+2x+5x=+99-6+12

We simplify left and right side of the equation.
+7x=+105

We divide both sides of the equation by 7 to get x.
x=15

See similar equations:

| x-1/3-x-1/2=5/4 | | (5x+1)(x-3)=(x-5)(5x-2)+2 | | 3(k-1)=k+6 | | y=50x+4 | | 4-5y=7-2(y-6) | | p=18-(2-3p) | | 49s-26=107 | | 6x-(5+2x)+5=x | | 5(p-1)=p+5 | | 5/8÷25/16= | | 2-4x=3x-5 | | e(2x+1)+7e(x)-15=0 | | 7x=31412+312 | | 36t^2+128t^3=9 | | -36t^2+128t^3=9 | | 5+3=x-3x-2x | | -72*t^2+256*t^3=18 | | x^10=1.55 | | x^10=15 | | 140x+x=180 | | -4x^3=-4x | | -2+a-b+1=0 | | 1+a+2b+4=0 | | x+4*3-4=65 | | (x-9)(x-12)=0 | | a=bx+cx^3 | | 7x-2y+4=o | | 2x-8x+13=26-x+14 | | 4-4x=4x+4 | | 3a+3b-2ab=0 | | 16-3x=11-21x | | 8-6x=9+x |

Equations solver categories